Recent Advances in Artificial Sensory Neurons: Biological Fundamentals, Devices, Applications, and Challenges - Zhong, Shuai; Su, Lirou; Xu, Mingkun; Loke, Desmond; Yu, Bin; Zhang, Yishu; Zhao, Rong (Nano-Micro Letters, 2024)
Spike-based neural networks, which use spikes or action potentials to represent information, have gained a lot of attention because of their high energy efficiency and low power consumption. To fully leverage its advantages, converting the external analog signals to spikes is an essential prerequisite. Conventional approaches including analog-to-digital converters or ring oscillators, and sensors suffer from high power and area costs. Recent efforts are devoted to constructing artificial sensory neurons based on emerging devices inspired by the biological sensory system. They can simultaneously perform sensing and spike conversion, overcoming the deficiencies of traditional sensory systems. This review summarizes and benchmarks the recent progress of artificial sensory neurons. It starts with the presentation of various mechanisms of biological signal transduction, followed by the systematic introduction of the emerging devices employed for artificial sensory neurons. Furthermore, the implementations with different perceptual capabilities are briefly outlined and the key metrics and potential applications are also provided. Finally, we highlight the challenges and perspectives for the future development of artificial sensory neurons. Highlights: 1 Biological fundamentals and recent progress of artificial sensory neurons are systematically reviewed. 2 Basic device, performance metrics, and potential applications of artificial sensory neurons are summarized. 3 Challenges for the future development of artificial sensory neurons are discussed.